1998
DOI: 10.1073/pnas.95.8.4619
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutation reveals a central role for SR-BI in hepatic selective uptake of high density lipoprotein cholesterol

Abstract: Scavenger receptor BI (SR-BI) is a cell surface receptor that binds high density lipoproteins (HDL) and mediates selective uptake of HDL cholesteryl esters (CE) in transfected cells. To address the physiological role of SR-BI in HDL cholesterol homeostasis, mice were generated bearing an SR-BI promoter mutation that resulted in decreased expression of the receptor in homozygous mutant (designated SR-BI att) mice. Hepatic expression of the receptor was reduced by 53% with a corresponding increase in total plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
211
1
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(235 citation statements)
references
References 30 publications
18
211
1
4
Order By: Relevance
“…7 Consequently, hepatic overexpression of SR-BI results in decreased plasma HDL cholesterol levels, [8][9][10] whereas SR-BI knockout mice have increased plasma HDL cholesterol. 11,12 Interestingly, hepatocyte SR-BI appears to accelerate reverse cholesterol transport in vivo in the face of decreased plasma HDL cholesterol levels, 13 which is in line with studies demonstrating that hepatic SR-BI expression protects against atherosclerosis development in mouse models. 14,15 Hepatic SR-BI expression is also linked to biliary cholesterol secretion in a process that is less well understood than selective uptake.…”
supporting
confidence: 62%
“…7 Consequently, hepatic overexpression of SR-BI results in decreased plasma HDL cholesterol levels, [8][9][10] whereas SR-BI knockout mice have increased plasma HDL cholesterol. 11,12 Interestingly, hepatocyte SR-BI appears to accelerate reverse cholesterol transport in vivo in the face of decreased plasma HDL cholesterol levels, 13 which is in line with studies demonstrating that hepatic SR-BI expression protects against atherosclerosis development in mouse models. 14,15 Hepatic SR-BI expression is also linked to biliary cholesterol secretion in a process that is less well understood than selective uptake.…”
supporting
confidence: 62%
“…Loss-of-function variants in human SCARB1 (SR-BI) were associated with increased in circulating HDL-C levels [37]. Likewise, Scarb1 mutations in mice also resulted in increased HDL-C levels [38]. We have previously reported that HDL-delivery of miRNAs to hepatocytes in vitro requires SR-BI [13].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of SRBI following infection with recombinant adenoviruses or in transgenic mice resulted in reductions in plasma HDL cholesterol [36][37][38][39] and was associated with a substantial increase in the cholesterol content of gallbladder and hepatic biles. 38,40 Disruption of the Srb1 gene promoter with subsequently decreased SRBI protein expression increased plasma HDL levels 41 and decreased biliary cholesterol. 40 The close linkage of biliary cholesterol and SRBI protein expression is further supported by a negative correlation between the cholesterol content of bile and HDL levels.…”
Section: Discussionmentioning
confidence: 99%